Beyond 3G : bringing networks, terminals and the Web together : LTE, WiMAX, IMS, 4G devices and the mobile Web 2.0 - Sauter, Martin (John Wiley & Sons, 2009)
Giving a sound technical introduction to 3GPP LTE and SAE, this book explains the decisions taken during standardization while also examining the likely competition for LTE such as HSPA+ and WiMAX. As well as looking at next generation network technologies, Beyond 3G - Bringing Networks, Terminals and the Web Together describes the latest mobile device developments, voice and multimedia services and the mobile web 2.0. It considers not only how the systems, devices and software work but also the reasons behind why they are designed in this particular way. How these elements strongly influence.